High-throughput screening of dual-target inhibitors for SARS-CoV-2 main protease and papain-like protease from Chebulae Fructus: in silico prediction and experimental verification - Wang, Changjian; Cao, Yipeng; Yang, Qi; Wang, Xinyue; Yang, Zhiying; Yang, Jingjing; Li, Xinru; Li, Bin; Wang, Yuefei; Zhang, Min (Frontiers in Microbiology, 2024)
BackgroundThe unavoidable propagation of the coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has underscored the urgent requirement for efficacious therapeutic agents. The dried fruit of Terminalia chebula Retz., namely Chebulae Fructus, is widely used for treating bacterial and viral infectious diseases, which was witnessed to perform anti-SARS-CoV-2 activity in recommended Chinese patent medicine.AimSARS-CoV-2 main protease (Mpro) and papain-like protease (PLpro) present essential effects on SARS-CoV-2 replication and transcription, considering as the attractive targets for therapeutic intervention. In this study, we focused on the dual-target to obtain broad-spectrum antiviral candidates from Chebulae Fructus.MethodsThe identified compounds from Chebulae Fructus were used to build a library in a previous study, which were evaluated by molecular docking to screen potential antiviral agents. The SARS-CoV-2 Mpro and PLpro were expressed in E. coli cells and purified. Fluorescence resonance energy transfer (FRET) and surface plasmon resonance (SPR) were utilized to verify the affinity with dual targets. SARS-CoV-2 wild-type, Omicron BA.5 and Omicron EG.5 variants were employed to validate their antiviral activities in vitro. Molecular dynamics simulation was conducted via Gromacs 2022 software in 500 ns to unveil the conformation stability.ResultsTargeting on Mpro and PLpro, eight compounds were screened as the potential dual-target inhibitors in molecular docking. In FRET and SPR assays, 1,2,3,4,6-penta-O-galloyl-β-D-glucose (PGG) and 1,2,3,6-tetra-O-galloyl-β-D-glucose (TGG) showed good inhibitory activities with IC50 values ranging from 1.33 to 27.37 μM, and affinity with KD values ranging from 0.442 to 0.776 μM. Satisfactorily, both PGG and TGG display antiviral activity in vitro with EC50 values ranging from 3.20 to 37.29 μM, suggesting as the promising candidates against SARS-CoV-2. In molecular dynamics simulation study, the complexes of Mpro-PGG, Mpro-TGG, PLpro-PGG, and PLpro-TGG exhibited stability over 500 ns period, unveiling the potential interactions.ConclusionPGG and TGG are the promising dual-target inhibitors of SARS-CoV-2, which may avoid drug resistance and have a good development prospect. The outcomes of this study provide an effective strategy to systematically explore the antiviral bioactive compounds from Chebulae Fructus.